DOPAMINA E ÁCIDO ASCÓRBICO: UMA ABORDAGEM UTILIZANDO VOLTAMETRIA CÍCLICA E SIMULAÇÃO COMPUTACIONAL - Praisner, Ricksson Antunes (2019)
As an important study compound, dopamine (DA) is of great interest to chemists and neuroscientists because it is linked to feelings of pleasure and feelings of reward, but mainly because its low blood levels are linked to Parkinson's disease. One of the major problems in detecting dopamine in the blood is the interferents present in it, such as ascorbic acid (AA), whose oxidation peak is close to the dopamine oxidation peak, resulting in spiked peaks, making quantitative electrochemical analysis impossible. . Many studies today focus on the development of electrodes so that there is greater separation and resolution of the DA and AA voltammetric peaks. In this work, DA was studied individually and together with AA at a concentration of 5 μM at pH 5, 7 and 8.1 via cyclic voltammetry. The results obtained and treated show that the dopamine oxireduction process is diffusion controlled. at all pHs studied. AA was studied at pH 7 at a concentration of 500μM individually and in conjunction with DA. For AA, studied in isolation, it was shown that the electrochemical process is also controlled by neutral pH diffusion, as well as for dopamine. Studies using square wave voltammetry showed no expected results, since no linearity of ip (peak current) versus f (frequency) and ip versus f 1/2 could be found. Obtaining the diffusion coefficient (D) of the dopamine oxireduction process in neutral medium cannot be calculated using the Levich equation, since no limit current plateau was found when the electrode rotation speed was performed, but such results suggest that the species is immobilized on the electrode, demonstrating an adsorptive behavior. Oxidation and reduction reactions of DA and AA were simulated via Digielch® software, similarly adjusted to the experimentally obtained voltammetric curve. A possible peak separation method was qualitatively evaluated, but the results suggest that the technique employed promises to serve as a means of AA and DA peak separation.